Heroic saga and classical epic in medieval Ireland - Miles, Brent (Studies in Celtic history, 2011)
'Original, innovative work which elucidates a number of individual narratives; but more significantly, by placing these texts in their proper intellectual context, the author demonstrates how the world of learning in eleventh- and twelfth-century Ireland really worked. He illuminates a world of medieval education and scholarship; he tells us (as no-one has done previously) what medieval Irish classicism was all about.' Dr Máire ni Mhaonaigh, St John's College, University of Cambridge. The puzzle of Ireland's role in the preservation of classical learning into the middle ages has always excited scholars, but the evidence from the island's vernacular literature - as opposed to that in Latin - for the study of pagan epic has largely escaped notice. In this book the author breaks new ground by examining the Irish texts alongside the Latin evidence for the study of classical epic in medieval Ireland, surveying the corpus of Irish texts based on histories and poetry from antiquity, in particular 'Togail Troi', the Irish history of the Fall of Troy. He argues that Irish scholars' study of Virgil and Statius in particular left a profound imprint on the native heroic literature, especially the Irish prose epic 'Táin Bó Cúailnge' ('The Cattle-Raid of Cooley'). BRENT MILES is a Fellow in Early and Medieval Irish, University College Cork.